THE EFFECT OF SAP IMPLEMENTATION, THE UTILIZATION OF REGIONAL FINANCIAL ACCOUNTING INFORMATION SYSTEMS AND THE ROLE OF THE INTERNAL AUDIT FUNCTION ON THE QUALITY OF LOCAL GOVERNMENT FINANCIAL REPORTS IN MEDAN CITY - Riyanti, Anita; Maisyarah, Renny; Siregar, Oktarini Khamilah (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The research analysis is to prove whether the application of SAP, the application of the use of regional financial accounting information systems and the role and function of internal audit have a positive and significant impact on the quality of the financial statements of the Medan City Government. The data analysis technique used is associative quantitative method. Primary data collection using a questionnaire study. The sample is 30 respondents. The results showed that the partial application of SAP had a positive and significant effect on the quality of the Medan City Government's financial reports. The application of the use of regional financial accounting information systems partially has a positive and significant effect on the quality of the financial statements of the Medan City Government. The application of the role and function of the internal audit partially has a positive and significant effect on the quality of the financial statements of the Medan City Government. The application of SAP, theapplication of the use of regional financial accounting information systems and the role and function of internal audit simultaneously have a positive and significant effect on the quality of the financial statements of the Medan City Government.